Performance comparison of novel chemical agents in improving oil recovery from tight sands through spontaneous imbibition - Hai Huang (KeAi Communications Co., Ltd., 2019)
Abstract Tight sands are abundant in nanopores leading to a high capillary pressure and normally a low fluid injectivity. As such, spontaneous imbibition might be an effective mechanism for improving oil recovery from tight sands after fracturing. The chemical agents added to the injected water can alter the interfacial properties, which could help further enhance the oil recovery by spontaneous imbibition. This study explores the possibility of using novel chemicals to enhance oil recovery from tight sands via spontaneous imbibition. We experimentally examine the effects of more than ten different chemical agents on spontaneous imbibition, including a cationic surfactant (C12TAB), two anionic surfactants (O242 and O342), an ionic liquid (BMMIM BF4), a high pH solution (NaBO2), and a series of house-made deep eutectic solvents (DES3–7, 9, 11, and 14). The interfacial tensions (IFT) between oil phase and some chemical solutions are also determined. Experimental results indicate that both the ionic liquid and cationic surfactant used in this study are detrimental to spontaneous imbibition and decrease the oil recovery from tight sands, even though cationic surfactant significantly decreases the oil–water IFT while ionic liquid does not. The high pH NaBO2 solution does not demonstrate significant effect on oil recovery improvement and IFT reduction. The anionic surfactants (O242 and O342) are effective in enhancing oil recovery from tight sands through oil–water IFT reduction and emulsification effects. The DESs drive the rock surface to be more water-wet, and a specific formulation (DES9) leads to much improvement on oil recovery under counter-current imbibition condition. This preliminary study would provide some knowledge about how to optimize the selection of chemicals for improving oil recovery from tight reservoirs.